Dispersed Urban Spatial Structure and Increased Urban Greenness Could Reduce Intra-City Health inequalities in England - Jia, Yinghui; Wang, Lan; Lou, Jiankun (AESOP, 2024)
The persistence of socioeconomic health inequalities has garnered substantial attention, and a few researchers have explored the impact of neighborhood greenness on mitigating it. However, it remains unclear whether comprehensive planning can address this issue. In this study, we evaluated intra-city health inequality in 105 cities in England and examined the impact of urban spatial structure (measured by dispersion) on it, with adjustment for city size, population density, urban greenness, development level, income gap, and aging. Results revealed that the dispersion of urban population (β=-0.179, p=0.043) and urban greenness (β=-0.147, p=0.087) exhibited significant negative relationships with intra-city health inequalities, while the income gap showed a significantly positive relationship ( β =0.500,, p00.001). These findings underscore the critical role of city comprehensive planning in mitigating health inequalities. Keywords: urban inequality, city comprehensive planning, urban spatial structure, health and well-being
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024